2018
DOI: 10.31393/bba32-2018-06
|View full text |Cite
|
Sign up to set email alerts
|

Somatotypological features of acrobat girls in different periods of ontogenesis

Abstract: The somatotypological characteristic of acrobats in the literature is insufficiently disclosed, especially from the position of the role of sports selection, training and competitive activities in the formation of somatotype in athletes, whose professional activity is marked by coordination, rhythm and artistic movements, and the early onset of the impact of intense physical activity on their body. The purpose of the work is to establish the peculiarities of the components of the somatotype of acrobats with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…In our previous work, it was found that female athletes in the pubertal ontogenetic period had significantly lower (p <0.05) calendar age compared to non-female athletes, indicating a significant re-certification of puberty in acrobatics, which, in our opinion, may be due to features sports selection and competitive sports activities [16]. Significant retardation in rates of puberty and biological maturity of female athletes has been found in other scientific studies [17,18].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In our previous work, it was found that female athletes in the pubertal ontogenetic period had significantly lower (p <0.05) calendar age compared to non-female athletes, indicating a significant re-certification of puberty in acrobatics, which, in our opinion, may be due to features sports selection and competitive sports activities [16]. Significant retardation in rates of puberty and biological maturity of female athletes has been found in other scientific studies [17,18].…”
Section: Discussionsupporting
confidence: 52%
“…Scientists consider such retardation of puberty as a consequence of the effects of hereditary factors, which are exacerbated by intense training, deficiency of the total body weight, in particular, its fat component [19]. In previous studies, we also found in acrobats a statistically significant decrease in body fat, which is indicated by the size of the endomorphic component of the somatotype, in all periods of ontogenesis [16].…”
Section: Discussionmentioning
confidence: 63%
“…The waist-hip index was used to assess the distribution of body fat and the body. Modern studies show that the mass of adipose tissue and its abdominal accumulation significantly affect the functional state of the cardiovascular system, increase the level of blood pressure even with normal BMI [15][16][17][18][19]. It has been determined that both boys (61 %) and girls (94 %) have a favorable gynoid type of fat deposition ("pear" type).The intermediate type ("avocado") was found in 39 % of boys and 6 % of girls, and the unfavorable android type ("apple") was not found in the surveyed students.…”
Section: Research Resultsmentioning
confidence: 99%
“…
Сарафинюк Л. А. доктор біологічних наук, професор, завідувач кафедри фізичного виховання та лікувальної фізичної культури Вінницький національний медичний університет імені М. І. Пирогова м. Вінниця, Україна Сарафинюк П. В. кандидат біологічних наук, доцент кафедри біології Вінницький державний педагогічний університет імені Михайла Коцюбинського м. Вінниця, Україна Хапіцька О. П. кандидат медичних наук, доцент кафедри внутрішньої медицини № 3 Вінницький національний медичний університет імені М. І. Пирогова м. Вінниця, Україна Лежньова О. В. кандидат медичних наук, доцент кафедри фізичного виховання та лікувальної фізичної культури Вінницький національний медичний університет імені М. І. Пирогова м. Вінниця, УкраїнаГармонійність розвитку організму в дитячому, підлітковому, юнацькому віці багато в чому визначає подальше життя і долю жінки як в медичному, так і в соціальному аспектах [1,2]. Адже в даний час майже у кожного третього підлітка виявляються «слабкі ланки» в певних системах організму, які неадекватно реагують на фізичні наванта-
…”
unclassified
“…Гармонійність розвитку організму в дитячому, підлітковому, юнацькому віці багато в чому визначає подальше життя і долю жінки як в медичному, так і в соціальному аспектах [1,2]. Адже в даний час майже у кожного третього підлітка виявляються «слабкі ланки» в певних системах організму, які неадекватно реагують на фізичні наванта-…”
unclassified